Evaluation of Efficacy and Safety of Botox in the Management of Facial Wrinkles - Yadav, Dr. Aditi; Goyal, Dr. Manoj; Tripathi, Dr. Adarsh; Verma, Dr. Ajay; Kumari, Dr. Gayatri; Nigam, Dr. Abhijeet (International Journal of Innovative Research in Medical Science, 2017)
Throughout the evolution of aging, fine lines, facial wrinkles and texture have been persistent concerns for women. Some research reveals that this concern is legitimate and related to self-image and age related discrimination. There are a number of different causes of these fine lines and facial wrinkle lines, such as aging, sun exposure gravity and chronic pulling of mimetic muscles and hyperactive muscles on the face. Among these, pulling by mimetic muscles on the skin not only involves facial expression but also has a great role in forming facial wrinkle lines as a result of repetitive action, such as dynamic or hyperkinetic wrinkle lines. Hyperkinetic/ dynamic/long term facial wrinkles seem to contribute to the cause of many undesired facial rhytides and furrow and to the development of soft tissue ptosis in many facial regions. This can occur naturally over time and is identified by certain biochemical, histological and physiological changes that are enhanced by environmental exposure.[1] The main factors accelerating the process of aging include hereditary factors, smoking and ultraviolet radiation. These dynamic process cause skin changes include skin sagging, fine wrinkling and deepening animation. Facial muscle pulls direct on the skin resulting in animation lines. In the upper face the skin muscle attachment accentuates the wrinkling process.[2] The pattern of facial wrinkles are predetermined during late childhood and carried out subconsciously through adulthood. Thus, repetitive muscle actions lead to hyperfunctional facial wrinkle lines. There are basically 4 patterns of facial wrinkles of upper face: 1) Horizontal frontal forehead wrinkling occurs during Brow lifting by the action of the frontalis muscle. 2) Deep vertical glabellar lines,by the action of corrugator supercilli muscles and the medial portion of orbicularis oculi when a person is frowning. 3) Horizontal lines at the frontal nasal groove are formed during frowning by the action of procerus muscle. 4) Lateral canthal lines (crow’s feet) formed by the action of orbicularis oculi during squeezing.[2] The treatment for this change over time can be multiple, from skin care products, to energy based therapies (lasers, light sources, and radiofrequency devices) to Botulinum toxins, dermal filler, fat graft etc. Numerous procedures designed to treat hyper functional facial lines namely, rhytidectomy, liposuction, brow lift, dermabrasion, chemical peel, collagen injections do not address the underlying problems and are associated with various complications. Botulinum toxin A has been safely and effectively used for the treatment of various disorders, including cosmetic facial surgery for more than a decade in a safe and effective manner. Over a year there has been an increasing array of use of botulinum toxin in cosmetic facial surgery. Glabellar furrow lines, forehead furrows, crow’s feet and other muscle groups, which are a result of pull on skin by underlying facial mimetic musculature; have been treated with the toxin.[1] Botulinum toxin acts at the neuromuscular junction by irreversibly inhibiting the release of acetylcholine. Cosmetic denervation of the hyper functional musculature using Botulinum toxin has gained growing popularity over the years. Since 1987, botulinum toxin A (BTX-A) has been used to denervate certain muscles of facial expression that are in part responsible for static facial rhytids. It has been applied to rhytids in the glabella, forehead, lateral canthal skin, and neck. Additional uses in Oral and Maxillofacial surgery include the denervation of hypertrophic or hyperactive masticatory muscles for cosmetic and functional purposes.[3] Clostridium botulinum was implicated over 100 years ago as the cause of muscle paralysis secondary to food poisoning. This gram positive anaerobic bacterium produces the most potent neurotoxin known to mankind. Seven distinct antigenic botulinum toxin (A, B, C, D, E, F and G) produced by different strains of Clostridium Botulinum have been described. Human disease is caused by five of these serotype (A, B, E, F and G). Type A is the strongest, followed by type E and F which are potentially of value in patients who developed antibodies to type A.[4] Clostridium botulinum has been in therapeutic use since the 1970’s. Scott is largely responsible for the initial clinical use of botulinum toxin in the treatment of strabismus where botulinum toxin injected into extraocular muscles results in the selective muscle paralysis and improves ocular alignment. Since that time, numerous other conditions including dystonias i.e. (blepharospasm and torticollis), involuntary muscle hyperactivity i.e (hemifacial spasm, tremors and tics) and spasticity (as in multiple sclerosis and cerebral palsy) have been treated successfully with botulinum toxin.[4] Facial rejuvenation has been revolutionized by the use of botulinum toxin over the past 15 years with safe use by clinicians using botulinum toxin type A producing excellent cosmetic results.[4] Considering the past 50 years of cosmetic facial surgery, there has been no other treatment that parallels the efficacy, ease, expense, and patient satisfaction as has botulinum toxin.[5] This study was done to evaluate the effect of Botulinum toxin type A in the management of facial wrinkles